Comparison of land use change in payments for environmental services and National Biological Corridor Programs. (April 2017) - Wood, Margot A.; Sheridan, Ryan; Feagin, Rusty A.; Castro, Jose Pablo; Lacher, Thomas E.
Highlights: Natural experiment used to understand land use change in areas of PES targeting. Decreased forests within four years of study. Increase pasture and bare ground features. Increased changes seen within biological corridor. PES properties had least amount of forest loss. Abstract: Costa Rica established the National Biological Corridor Program in 2006. Under the National Biological Corridor Program, the long-running Payment for Environmental Services Program was newly prioritized into biological corridors throughout the country. The National Biological Corridor Program caused a nationwide spatial shift in placement of payments for environmental services throughout Costa Rica. We classified ASTER 15-m resolution imagery in a central Costa Rica corridor connecting the eastern and western protected areas networks to analyze the change in forests during the National Biological Corridor Program with its targeted payments for environmental services effort. We used object-based classification methods, and compared land cover changes over an initial four-year period of corridor policy enactment. We calculated the changes within PES properties and outside of PES regions, and we also calculated forest patch metrics during the same time period. Results indicate a decline in forest cover over the study period, along with an increase in urban and pasture land covers, with higher change and loss of forest centered inside of the biological corridor, near the construction area for the new San Carlos highway, and within eastern pasture areas. We also saw a higher percentage of forest loss inside of the biological corridor area as compared to areas outside of the biological corridor. Forest loss was drastically less within current and historic PES properties, as compared to the overall study region. Across the entire study region, patch metrics show a decrease in the number of patches and a slight decrease in average patch size. These results suggest that current and past designation of PES prevents forest loss within PES properties while the current designation of priority conservation status via the National Biological Corridor Program is not increasing connectivity and forest conservation. This is shown by increased land use change and a decrease in forest associated with biological corridor designation. These results are antithetical to the goals of the National Biological Corridor Program.